Панська сільська садиба ХІХ ст. як культурна форма (на матеріалі Полтавщини та Чернігівщини) - Будзар, М. (Народна творчість та етнографія, 2006)
The topic of country seat of the 19th century as a cultural form of Ukraine attracts attention of various researchers in the last decade. During a long historical time such house was not only an economical centre but cultural, political and life of elite as well. It has to be analysed from the point of view of cultural studies as a product of material work and as a cultural community. In historical destiny of certain places country seats played a great role because they served as imperial nests of tsardom and oppositional moods of “shlyakhta” at the same time. In this work some peculiarities of the social and cultural life of the country seat of Poltava and Chernigiv regions in the 19th century have been analysed as well as the factors of its existence as a cultural form.